Dryades w Historia Augusta a problem metodologii badań nad Celtami - Wawrzyniak, Kacper (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
Augustan History contains passages about druidesses who foretell the future for emperors. Analysis of Historia Augusta results in the conclusion that this information is false. To confirm this statement, verification of the rest of the preserved material is necessary. Considering this, an unequivocal solution to the activities of druidesses in the third century CE is not satisfying.